(3JMQjQGJ GdefUhQj Ydi WjHI GdfTQ aj GdbQGAGJ GdYTQs - (3Ydj GdefUhQjs; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi Gddg JYGdi Ydi GdefUhQj ZaQ Gddg JYGdi dhGdOjg hdLejY GdeSedjf gPG eG JjSQ LeYg aj HYV GdBjGJ ef JMQjQ GdWQb hGdQGhjGJ s
(3BNQgG (B:s
(3ChdG Jgdjd hdG JMejO aj Chd GdaGJMI hGddg CYde hfNJe Hbhdg JYGdi ChdFc Ydi gOi ef QHge hChdFc ge GdeadMhf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B42 - (3U(B69s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1118s
Keywords: (3GdbQGAGJ hGdJLhjOs